Impact of nurse's worked hours on medication administration near-miss error alerts. (2nd October 2020) - Westley, Jlynn A.; Peterson, Jessica; Fort, Daniel; Burton, Jeffrey; List, Robert
ABSTRACT: Long working hours have been shown to negatively impact adverse events in health care. In this study, a retrospective correlational design was used to evaluate the relationship between working hours and near-miss medication error alerts. During a two-year period, 5372 nurses triggered 420, 706 near-miss alerts on 9, 285, 786 medication administrations. Nurses who worked 60 h or more in a week yielded an average near-miss rate of 4.0% compared to 3.0% ( p <.001) for nurses who did not. Nurses working extended hours had a significantly increased risk of triggering a near-miss alert compared to those not working extended hours.